Reconstruction of built-up urban areas taking into account accessibility to limited mobility population groups: the case of Krasnodar - E. P. Shnurnikova; S. P. Gorzova; V. V. Kononenko (Vestnik MGSU)
Introduction. The development of a comfortable living environment for persons with disabilities is one of the most important tasks in the modern world. To a large extent, its implementation depends on housing conditions of wheelchair users, as well as principles of their settlement in multi-apartment residential buildings in cities. Physical barriers in the architectural environment are the most pressing problem hindering rehabilitation and socialization of disabled persons. Uncomfortable housing conditions can hinder therapeutic and preventive care aimed at health improvement, and physical barriers in housing and yard spaces can hamper the socialization of disabled residents. The problem is more relevant than ever, because due to the ongoing Special Military Operation, the number of physically challenged persons is growing fast. With this in mind, it is important to continue adapting residential buildings for limited mobility population groups and creating a more comfortable environment for all urban residents.Materials and methods. The article analyzes (1) the way wheelchair users take up residence in large-scale development areas in the post-war Krasnodar, (2) the settlement of wheelchair users in urban districts, (3) the residence of wheelchair users in buildings with a different number of storeys. Contradictions are identified between current urban development conditions and surrounding architecture, on the one hand, and the needs of limited mobility residents, including their socialization, on the other hand. Criteria for selecting design solutions are developed; recommendations are provided for the reconstruction of existing residential buildings, equipping and modernizing the urban environment, raising awareness of problems to be tackled by disabled persons.Results. A list of steps is proposed to solve problems of housing conditions and principles of resettlement of disabled persons. In particular, factors impeding the treatment, preventive care and socialization of wheelchair users are considered, and their elimination plan is proposed. The article provides a theoretical justification for techniques and principles of architectural design of buildings, taking into account the accessibility of standard residential buildings to limited mobility persons.Conclusions. The article describes methods and techniques for solving several most important problems of wheelchair users in Krasnodar, in particular, their accessible living environment. The appropriateness of the settlement of disabled persons in the existing urban development and reconstruction of this architectural environment were analyzed; methods for designing buildings that meet the housing requirements of limited mobility persons were presented. Also, a social approach to developing a comfortable living environment for such members of society was formulated and analyzed to ensure their integration into the life of society, equal access to infrastructure, work and education.